2020
DOI: 10.1101/2020.01.24.917260
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptional analysis supports the expression of human snRNA variants and reveals U2 snRNA homeostasis by an abundant U2 variant

Abstract: Although expansion of snRNA genes in the human genome and sequence variation in expressed transcripts were both identified long ago, no study has comprehensively analyzed which genes are transcriptionally active. Here, we use comprehensive bioinformatic analysis to differentiate between similar or identical genomic loci to determine that 49 snRNA genes are actively transcribed. This greatly expands on previous observation of sequence variation within snRNA transcripts. Further analysis of U2 snRNA variants rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…However, variants such as U2-2P, U4-2, and multiple U5 snRNAs exhibit prolonged stability and higher levels of expression as compared to the majority of snRNA variant genes. Together with a recent study indicating that snRNA genes exhibit varying levels of occupancy by transcription factors and RNA polymerase II (Kosmyna et al 2020), our data indicate that both transcription rates and snRNA stability determine variant snRNA abundances.…”
Section: Nearly All Snrna Variants Are Less Stable Than Their Canonic...supporting
confidence: 81%
See 1 more Smart Citation
“…However, variants such as U2-2P, U4-2, and multiple U5 snRNAs exhibit prolonged stability and higher levels of expression as compared to the majority of snRNA variant genes. Together with a recent study indicating that snRNA genes exhibit varying levels of occupancy by transcription factors and RNA polymerase II (Kosmyna et al 2020), our data indicate that both transcription rates and snRNA stability determine variant snRNA abundances.…”
Section: Nearly All Snrna Variants Are Less Stable Than Their Canonic...supporting
confidence: 81%
“…Most snRNA genes have been identified using computational approaches and annotated as being pseudogenes due to sequence differences. However, only a small number have been manually evaluated or studied experimentally (Denison et al 1981;O'Reilly et al 2013;Vazquez-Arango et al 2016;Kosmyna et al 2020). Here, we refer to the most abundantly expressed and biochemically studied snRNA within each family as the "canonical" snRNA, and the remaining snRNAs as "variants."…”
Section: Resultsmentioning
confidence: 99%
“…4C). Out of the two major isoforms of U2, U2-1 shows more efficient deposition of the Sm ring and incorporation into snRNP complexes than U2-2 (Kosmyna et al 2020), and we hypothesized that failure of assembly into an snRNP complex might be associated with U2:U2 dimerization. However, analysis of the exact sequences of U2:U2 overlapping chimeras showed that out of 223 reads that could be assigned to specific U2 isoforms, 162 were of the U2-1:U2-1 type, and 59 were U2-1:U2-2 chimeras, suggesting that both U2 isoforms may form homo-and heteromeric intermolecular interactions.…”
Section: Homodimerization Of Human and Yeast Rnasmentioning
confidence: 99%
“…Most overlapping chimeras in U2 included the sequence of stem loop III, downstream of the Sm binding site, suggesting that in a fraction of U2 molecules found in the cell, stem loop III is unfolded and forms homomeric intermolecular interactions (Figure 4). Out of the two major isoforms of U2, U2-1 shows more efficient deposition of the Sm ring and incorporation into snRNP complexes than U2-2 (Kosmyna, et al 2020), and we hypothesized that failure of assembly into an snRNP complex might be associated with U2:U2 dimerization. However, analysis of the exact sequences of U2:U2 overlapping chimeras showed that out of 223 reads that could be assigned to specific U2 isoforms, 162 were of the U2-1:U2-1 type, and 59 were U2-1:U2-2 chimeras, suggesting that both U2 isoforms may form homo- and heteromeric intermolecular interactions.…”
Section: Resultsmentioning
confidence: 99%